Security concerns over the ISIS in Iraq and Syria: should Turkey join NATO? - Ahsan, Abdullahil (Turkey Agenda, 2014)
The question of Turkey’s participation in the fight against the ISIS group in Iraq and Syria is making news and has turned to be a subject of debate in international affairs. President Obama has called for this war and at least ten other countries immediately declared their resolve to join the war. But they want Turkey to join. Because, “…our expectation is that Turkey, as a NATO ally, is going -- just by virtue of her geography -- is going to be a partner in this effort, and they indicated that they would be and that they want to be. But it's up to Turkish leaders and the Turkish people to determine how and when that is manifested,” Pentagon Press Secretary Navy Rear Adm. John Kirby said during a press briefing on September 12. However, Turkish officials have remained more reserved about Turkey's possible role in the conflict. Why? Isn’t it an obligation on the part of Turkey, a NATO member, to join this battle? Isn’t it in Turkey’s own interest to crash these cancer-type extremists?